Increase in perceived stress is correlated to lower heart rate variability in healthy young subjects - Silva, Ana Gabriela Câmara Batista da; Araujo, Diego Neves; Costa, Amanda Caroline Muñoz; Dias, Bruna Alice Lima; Fregonezi, Guilherme Augusto de Freitas; Dias, Fernando Augusto Lavezzo (Acta Scientiarum. Health Sciences, 2015)
Emotional stress is a risk factor for cardiovascular disease. Decreased heart rate variability (HRV) is associated to increased mortality rates in certain heart diseases. Current study assessed the co-relation between perceived stress and HRV parameters. The correlation between psychological stress, measured by the perceived stress scale (PSS-14), and HRV parameters obtained during 5 min. at rest was evaluated. Data from 35 healthy young volunteers demonstrated a significant correlation between PSS-14 scores and Low Frequency-LF (ms2) by frequency domain HRV analysis. Other variables such as High Frequency and Standard Deviation of R-R intervals had also negative coefficients but did not have any significant correlation with PSS-14. No correlation between PSS-14 and sympathovagal balance parameters was found. Data interpretation demonstrated that increase in perceived stress was correlated to decrease in heart rate variability, which may point out an important mechanism in cardiovascular pathophysiology that should be further investigated.